2010
DOI: 10.1111/j.2042-3306.2010.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The workload and plasma ion concentration in a training match session of high‐goal (elite) polo ponies

Abstract: SummaryReasons for performing study: This study was designed to consider the complexity of the physical effort inherent to horses in polo competitions and the absence of reports in the literature on the effort, intensity and electrolyte changes resulting from a collective team training session aimed at preparing for a polo championship. Objectives: To determine the effort and ion changes caused by an outdoor polo training match for a 25 goal handicap (elite) based on physiological variables including acid-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 28 publications
7
37
0
8
Order By: Relevance
“…Our results indicated that, in the equine, the elevation mechanisms these cardiac biomarkers may be similar. The standardization of the cardiac biomarkers through kinetic study after exercise, training or clinical evaluation, considering their half-life, is the more technical procedure, because it improves the accuracy of significance of the response [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that, in the equine, the elevation mechanisms these cardiac biomarkers may be similar. The standardization of the cardiac biomarkers through kinetic study after exercise, training or clinical evaluation, considering their half-life, is the more technical procedure, because it improves the accuracy of significance of the response [31].…”
Section: Discussionmentioning
confidence: 99%
“…Conforme Ferraz et al (2010), cavalos participantes de uma partida treino de polo, considerados de alto handicap, desempenharam um esforço de alta intensidade com alterações transitórias nos eletrólitos e equilíbrio ácido-base de potencial relevância. Neste contexto, Babusci & López (2006) comentaram que em cavalos desidratados e com transtornos eletrolíticos graves, ocorreram alterações no potencial de membrana e estes sofreram taquicardias ventriculares com influência direta no desempenho atlético.…”
Section: Introductionunclassified
“…According to FERRAZ et al (2010), a possible mechanism to explain the elevation of serum concentrations of sodium is the exchange of ions and water that occurs between the active and inactive muscles. Dehydration increases the renal reabsorption of sodium so as to maintain the osmotic balance (MARTINS et al, 2005).…”
Section: Parametersmentioning
confidence: 99%